Systematic trends in YAlO3, SrTiO3, BaTiO3, BaZrO3 (001) and (111) surface ab initio calculations - Eglitis, Roberts; Purans, Juris; Popov, Anatoli I.; Jia, Ran (World Scientific Publishing, 2019)
The paper presents and discusses the results of performed calculations for YAlO3 (111) surfaces using a hybrid B3LYP description of exchange and correlation. Calculation results for SrTiO3, BaTiO3 and BaZrO3 (111) as well as YAlO3, SrTiO3, BaTiO3 and BaZrO3 (001) surfaces are listed for comparison purposes in order to point out systematic trends common for these four ABO3 perovskite (001) and (111) surfaces. According to performed ab initio calculations, the displacement of (001) and (111) surface metal atoms of YAlO3, SrTiO3, BaTiO3 and BaZrO3 perovskite, upper three surface layers for both AO and BO2 (001) as well as AO3 and B (111) surface terminations, in most cases, are considerably larger than that of oxygen atoms. The YAlO3, SrTiO3, BaTiO3 and BaZrO3 (001) surface energies for both calculated terminations, in most cases, are almost equal. In contrast, the (111) surface energies for both AO3 and B-terminations are quite different. Calculated (111) surface energies always are much larger than the (001) surface energies. As follows from performed ab initio calculations for YAlO3, SrTiO3, BaTiO3 and BaZrO3 perovskites, the AO- and BO2-terminated (001) as well as AO3- and B-terminated (111) surface bandgaps are almost always reduced with respect to their bulk bandgap values. ---- / / / ---- This is the preprint version of the following article: Roberts Eglitis, J. Purans, A. I. Popov and Ran Jia,Systematic trends in YAlO3, SrTiO3, BaTiO3, BaZrO3 (001) and (111) surface ab initio calculations, JInternational Journal of Modern Physics B, Vol. 33, No. 32 (2019) 1950390, DOI https://doi.org/10.1142/S0217979219503909, which has been published in final form at https://www.worldscientific.com/doi/abs/10.1142/S0217979219503909. This article may be used for non-commercial purposes in accordance with World Scientific Publishing Terms and Conditions for Sharing and Self-Archiving. The copyright of this work belongs to the publisher.
We greatly acknowledge the financial support via Latvian-Ukrainian Joint Research Project No. LV-UA/2018/2, Latvian Council of Science Grant No. 2018/2-0083 “Theoretical prediction of hybrid nanostructured photocatalytic materials for efficient water splitting”, Latvian Council of Science Grant No. 2018/1-0214 as well as ERAF Project No. 1.1.1.1/18/A/073.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Ab initio calculation; YAlO3; (111) surfaces; surface energies; B3LYP